Impacts of climate-driven insect population change on sawtimber provisioning, carbon sequestration, and water retention: a case study of bark beetle outbreaks in the USA - Haojie Chen; Matthew R. Sloggy; Samuel W. Flake; Samuel Evans; Charles J. Maxwell (Frontiers in Forests and Global Change)
A key issue in landscape management, whether public or private, is the mitigation of disturbance events that impact vegetation, ecosystem health, and thus ecosystem services (ESs). Although many studies have found significant tree mortality due to insect infestations, there is still insufficient understanding of how these infestations alter ESs and their associated economic values. Addressing this research gap can assist forest managers and decision-makers in refining and implementing adaptive management practices and policies, while enhancing the resilience of forests and their ESs. We investigated the impacts of bark beetle outbreaks on three ESs (timber provisioning, water retention, and carbon sequestration) in the Lake Tahoe region of Northern California and Northern Nevada. Using the landscape simulation model LANDIS-II, we examined differences between a business-as-usual management scenario and an enhanced management scenario with respect to the amount of aboveground tree biomass and ESs impacted by beetle outbreaks. Since insect infestation is also influenced by climate, each of the two management scenarios considered three different climate scenarios: a scenario with average historical climate (no climate change); a warmer, wetter scenario from the Model for Interdisciplinary Research on Climate (MIROC); and a hotter, drier scenario from the Centre National de Recherches Météorologiques (CNRM). Results show that a warmer and drier climate results in more severe beetle-induced tree mortality than a wetter and cooler climate, resulting in greater negative impacts to ESs. The estimated loss of ES value is approximately $0.2 to $0.8 million USD per year. Enhanced management is more capable than business-as-usual practices to prevent beetle damages to trees and ESs.